Homoeopathic Treatment of Childhood Herpes Zoster—A Case Series - Parveen, Suraia; Ahmed, Zeeshan; Das, Subhrasankha (Homœopathic Links, 2023)
Background Herpes zoster (HZ) is a relatively rare infectious disease in the paediatric population as compared to adults, occurring due to the reactivation of latent varicella-zoster virus that persists in the posterior root ganglion. HZ can develop any time after the primary infection and is characterised by grouped vesicular rashes limited to single dermatome. Diagnosis is based on a distinct clinical appearance of HZ. Its clinical course is variable, and it requires prompt medical treatment to prevent the complications. In conventional method, antiviral and other treatment modalities are available; however, these are fraught with potentially severe side effects and is expensive that demands an alternative method of treatment.Methods A case series of three children with HZ treated with individualised homeopathy is presented here. The cases are reported according to HOM-CASE guidelines and followed up with photographic documentation. The Modiﬁed Naranjo Criteria for Homeopathy (MONARCH) inventory was used as a tool for assessing the causal relationship between homeopathic intervention and clinical outcome.Results All cases of HZ were successfully cured with individualised homoeopathy within 10 days without any complication. Individual curative response of the homoeopathic medicine in each case was assessed through MONARCH which demonstrated a positive causal attribution of homeopathy.Conclusion Successful results of this case series suggest a positive response of individualised homeopathic medicines in the treatment of childhood HZ. The remissions of the HZ lesion presented in this case series may be attributed to homeopathic medicines in each case. Hence, this case series could serve as a basis for further research into the role of individualised homeopathic medicine in the treatment of childhood herpes zoster.
Keywords: children; herpes zoster; homeopathy; MONARCH